Phytoplankton fuel the energy flow from zooplankton to small nekton in turbid mangrove waters - Chew, L.L.; Chong, V.C.; Tanaka, K.; Sasekumar, A. (Inter Research, 2012)
Fish, zooplankton, seston, benthic microalgae and mangrove leaves were examined to investigate the trophic role of zooplankton in the food web of Matang estuaries. Despite the high turbidity and large amounts of detrital material in the water column, the study reveals that phytoplankton fuel the energy flow to zooplankton and small nekton in mangrove-fringed estuaries. The stable carbon isotope (δ13C) values and C/N ratios (7.2 to 8.2) of fine seston (<63 µm) in estuaries indicate the importance of phytoplankton (δ13C: −22.8 ± 0.6‰) to zooplankton (−23.4 to −18.2‰) nutrition, with a trophic contribution of 70 to 84%, whereas mangroves contributed <11%. In adjacent coastal waters, zooplankton (−19.2 to −15.1‰) grazed on both phytoplankton and benthic diatoms (−17.3 ± 1.24‰). Aggregated or mucilage-secreting diatoms (giving depleted δ13C values) were abundant in the estuarine seston, but did not appear to be consumed or assimilated by zooplankton. Stomach content analysis showed significant consumption of zooplankton, especially copepods (mainly Pseudodiaptomus annandalei), sergestids (Acetes spp.) and mysids by young and small nekton (<14 cm standard length) in mangrove estuaries, while δ13C values indicate the increasing importance of mangrove carbon to juvenile fish nutrition (8 to 44%). The range of δ15N values from primary producers to small predatory fish indicates 4 trophic levels (excluding true piscivores) in Matang estuaries, with zooplankton at the second and third trophic level.